Analisis Pengaruh Disiplin Kerja, Kompensasi Dan Motivasi Terhadap Kinerja Guru - Dewi, Kadek Melda Trisna; Wimba, I Gusti Ayu; Mahayasa, I Gede Aryana (Media Bisnis, 2025)
Teachers' performance is the result of work achieved in accordance with their responsibilities and authority to achieve goals effectively. Several factors influence the improvement of teacher performance, such as work discipline, compensation, and motivation. Work discipline refers to the actions of a teacher in adhering to the regulations that have been mutually agreed upon. Compensation is something received in return for the services contributed to their work. Meanwhile, motivation is something that creates an urge to achieve a goal. This research aims to determine the effect of work discipline, compensation, and motivation on teacher performance both partially and simultaneously. The research was conducted at SMK PGRI 1 Gianyar. The population of the study consists of 52 teachers from SMK PGRI 1 Gianyar. The sample was determined using a saturated sampling technique, resulting in 52 samples. Data were collected through interviews, documentation, and questionnaires measured with a Likert scale. The analysis technique used was multiple linear regression. The results show that work discipline has a positive and significant effect on teacher performance, compensation has a positive and significant effect on teacher performance, motivation has a positive and significant effect on teacher performance, and the independent variables simultaneously have a positive and significant effect on the dependent variable. The recommendation given is to improve work discipline, adjust compensation, and motivate teachers to enhance their performance at SMK PGRI 1 Gianyar.